ANALISIS KEMAMPUAN MEMBACA AL-QUR'AN SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VI SD NEGERI 249 BATU PALLA, BONTO KATUTE, KECAMATAN SINJAI BORONG, KABUPATEN SINJAI - Arni Susanti; ST. Khaerunnisa; Sitti Rohani; Muhammad Tang; Juhasdi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading the Qur’an correctly is a core competency in Islamic Religious Education. This study describes proficiency levels, reading errors, and influencing factors for sixth-grade students at SD Negeri 249 Batu Palla. A descriptive qualitative approach involved 16 students and teachers. Data were collected via tiered test: ta’awudz, basmalah, Surah Al-Bayyinah, then Juz 27–29 if fluent, or Iqra’ 6 to 1 if not, plus interviews. Results: 37.5% good, 12.5% sufficient, 50.0% low. Main errors: madd rules, similar letters, transition from Iqra’. Factors: limited time, imitation method, low family and community support. Qur’an literacy development requires synergy between schools, families, and communities.